The Distinctive Legal Features of Crimes Against Humanity (European Journal of Interdisciplinary Studies, 2016)
This research intends to analyze general features and elements of criminal acts against humanity. Also in this paper, special attention was paid to the distinctive features that are crucial in the legal classification of crimes against humanity as offenses punished with international acts and legal regulations of each state. The term Crime against humanity first appeared in the London Agreement of 8 August 1945 establishing the International Military Tribunal. In the course of the preparatory work, it had become apparent that certain crimes committed during the Second World War were not, strictly speaking, war crimes. These were crimes whose victims were of the same nationality as the perpetrators, or nationals of an allied State and were committed for different motives. As early as March 1944, the representative of the United States of America on the Legal Committee of the United Nations War Crimes Commission proposed that crimes committed against stateless persons or any other person by reason of their race or religion should be declared "Crimes against humanity". It suggests, in at least two distinct ways, the enormity of these offenses of the other criminal offenses. First, the phrase "crimes against humanity" suggests offenses that aggrieve not only the victims and their own communities, but all human beings, regardless of their community. Second, the phrase suggests that these offenses cut deep, violating the core humanity that we all share and that distinguishes us from other natural beings. This double meaning gives the phrase potency, but also an ambiguity we may trace back to the double meaning of the word "humanity". "Humanity" means both the quality of being human-humanness-and the aggregation of all human beings-humankind. Crimes against humanity, as defined by the Rome Statute of the International Criminal Court Explanatory Memorandum, "Are particularly odious offenses in that they constitute a serious attack on human dignity or grave humiliation or a degradation of human beings". They are not isolated or sporadic events, but are part either of a government policy or of a wide practice of atrocities tolerated by a government or a de facto authority. The law traditionally distinguishes between crimes against persons, crimes against property, crimes against public order, crimes against morals, and the like. Murder, extermination, torture, rape, political, racial or religious persecution and other inhumane acts reach the threshold of crimes against humanity only if they are part of a widespread or systematic practice.